Analisis Kebijakan Pemerintah tentang Guru dan Dosen :Kajian Perbandingan antar Negara - Hermanto, Edi (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
The purpose of this writing is to find out an analysis of government policies regarding teachers and lecturers: a comparative study between countries. This paper uses the library research method. The results of the research show that: 1) Law No. 14 of 2005 concerning Teachers and Lecturers has an impact on teachers, 2) Based on Article 8 it states that: "Teachers must have academic qualifications, competencies, educator certificates, be physically and mentally healthy, and have the ability to realize national education goals, 3) Professional educators who meet the qualification standards stipulated in article 8 of Law No. 14 of 2005 concerning Teachers and Lecturers which states that they are required to have academic qualifications, competencies, educator certificates, physically and mentally healthy, and have the ability to achieve national education goals